Targeting glucosylceramide synthase synergizes with C6-ceramide nanoliposomes to induce apoptosis in natural killer cell leukemia. Issue 6 (1st June 2013) - Watters, Rebecca J.; Fox, Todd E.; Tan, Su-Fern; Shanmugavelandy, Sriram; Choby, Jacob E.; Broeg, Kathleen; Liao, Jason; Kester, Mark; Cabot, Myles C.; Loughran, Thomas P.; Liu, Xin
Abstract: Natural killer (NK) cell leukemia is characterized by clonal expansion of CD3 − NK cells and comprises both chronic and aggressive forms. Currently no effective treatment exists, thus providing a need for identification of novel therapeutics. Lipidomic studies revealed a dysregulated sphingolipid metabolism as evidenced by decreased levels of overall ceramide species and increased levels of cerebrosides in leukemic NK cells, concomitant with increased glucosylceramide synthase (GCS) expression. GCS, a key enzyme of this pathway, neutralizes pro-apoptotic ceramide by transfer of a uridine diphosphate (UDP)-glucose. Thus, we treated both rat and human leukemic NK cells in combination with: (1) exogenous C6 -ceramide nanoliposomes in order to target mitochondria and increase physiological pro-apoptotic levels of long chain ceramide, and (2) 1-phenyl-2-palmitoylamino-3-morpholino-1-propanol (PPMP), an inhibitor of GCS. Co-administration of C6 -ceramide nanoliposomes and PPMP elicited an increase in endogenous long-chain ceramide species, which led to cellular apoptosis in a synergistic manner via the mitochondrial intrinsic cell death pathway in leukemic NK cells.